Effects of fluoxetine on protein expression of potassium ion channels in the brain of chronic mild stress rats - Chunlin Chen; Ling Wang; Xianfang Rong; Weiping Wang; Xiaoliang Wang (Elsevier, 2015)
The purpose of this study is to investigate the expression of major potassium channel subtypes in the brain of chronical mild stress (CMS) rats and reveal the effects of fluoxetine on the expression of these channels. Rats were exposed to a variety of unpredictable stress for three weeks and induced anhedonia, lower sucrose preference, locomotor activity and lower body weight. The protein expressions were determined by Western blot. CMS significantly increased the expression of Kv2.1 channel in frontal cortex but not in hippocampus, and the expression level was normalized after fluoxetine treatment. The expression of TREK-1 channel was also obviously increased in frontal cortex in CMS rats. Fluoxetine treatment might prevent this increase. However, the expression of Kv3.1 and Kv4.2 channels was considerably decreased in hippocampus after CMS, and was not affected by fluoxetine. These results suggest that different subtypes of potassium channels are associated with the pathophysiology of depression and that the therapeutical effects of fluoxetine may relate to Kv2.1 and TREK-1 potassium channels.